2022
DOI: 10.1111/desc.13296
|View full text |Cite
|
Sign up to set email alerts
|

Learning how to learn from social feedback: The origins of early vocal development

Abstract: Infants’ prelinguistic vocalizations reliably organize vocal turn‐taking with social partners, creating opportunities for learning to produce the sound patterns of the ambient language. This social feedback loop supporting early vocal learning is well‐documented, but its developmental origins have yet to be addressed. When do infants learn that their non‐cry vocalizations influence others? To test developmental changes in infant vocal learning, we assessed the vocalizations of 2‐ and 5‐month‐old infants in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Adult utterances are shorter in conversational turn‐taking than in a monologue (Marklund et al., 2015). By 5 months, infants expect social responses to their vocalizations (Elmlinger et al., 2022). Our results suggested that 9‐month‐old infants, when babbling, might have developed an expectation for rapid responses in interactions built from experiences with caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Adult utterances are shorter in conversational turn‐taking than in a monologue (Marklund et al., 2015). By 5 months, infants expect social responses to their vocalizations (Elmlinger et al., 2022). Our results suggested that 9‐month‐old infants, when babbling, might have developed an expectation for rapid responses in interactions built from experiences with caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Language acquisition in children usually progresses through a series of phases from one developmental milestone to the next, increasing the complexity, fluency, and consistency of the language. Early vocal development occurs in a sequential manner, resulting in the development of our complex human speaking capability which caused by social input (Cychosz, et al, 2021;Elmlinger et al, 2022;Ramírez-Esparza et al, 2017;Zhang & Ghazanfar, 2018). Regardless of the underlying theoretical language frameworks or explanatory models, agreement exists that it all begins with the first cry, followed by the production of vegetative and quasi-resonant noises until the first cooing sounds appear at about three months of age (Lang et al, 2019).…”
Section: Findings and Discussion Canonical Babbling And Comprehension...mentioning
confidence: 99%
“…An influential view has been that intentional communication develops through a four-step process of internalisation (Bruner, 1974;Vygotskij & John-Steiner, 1979) (note that these ideas are relatively compatible with the neurocomputational associative accounts we described in section 4). This type of model has been used to explain how infants learn to use pointing (Begus & Southgate, 2018;Kidd & Holler, 2009;Kovács et al, 2014;Wu & Gros-Louis, 2014) and vocalisations to communicate (Elmlinger et al, 2023;Ghazanfar & Zhang, 2016;Gros-Louis et al, 2006;. Can it also explain the emergence of intentional communication through gaze?…”
Section: Figure 4: Schematic Illustrating the Arguments Of Sections 4-6mentioning
confidence: 99%